The impact of pollution from hazardous and toxic materials (B3) waste on public health - Dahalan, Farrah Aini; Mulia, Mimin Indriani (Universitas Nahdlatul Ulama Surabaya, 2024)
Land pollution by B3 waste can have an impact on human health, the environment and even the sustainability of natural resources. In 2021, Indonesia produced around 60 tons of B3 waste from the industrial sector. In several industrial sectors, it was reported that several workers complained of health problems due to soil contamination by B3 waste. Some of the health impacts that may arise due to B3 waste pollution are acute to chronic health problems, skin and respiratory tract irritation, and decreased quality of life due to decreased health conditions. Therefore, effective B3 waste management is needed to prevent environmental pollution and protect human health.